Wear and corrosion properties of a B–Al composite layer on pure titanium. Issue 9 (1st May 2022) - Wang, Xinyu; Qu, Deyi; Duan, Yonghua; Peng, Mingjun
Abstract: A boriding and aluminizing two-step method was used to fabricate a B–Al composite layer on the surface of pure titanium. The composite layer was characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), nanoindentation, wear tests, and electrochemical experiments. For comparison, single boriding and single aluminizing treatments were performed on pure titanium. The results show that the surface morphology characteristics from the single boriding and single aluminizing treatments were transferred to the composite sample. The XRD pattern reveals that the B–Al composite layer also has XRD peaks of Al3 Ti+TiB2 +TiB. The SEM results revealed that the B–Al composite layer is composed of an outermost TiB2 layer, a TiB+Al3 Ti sublayer, an Al3 Ti layer, and an internal diffusion layer. The corrosion resistance of the composite sample is slightly better than that of the matrix, and the hardness is approximately 3 times higher than that of the matrix. The wear type is mainly abrasive wear, and the wear resistance is improved; with increasing temperature, the wear on the surface of the sample is intensified, and the wear resistance is reduced.